Progress in the Study of Colorectal Cancer Caused by Altered Gut Microbiota After Cholecystectomy - Ma, Yanpeng; Qu, Ruize; Zhang, Yi; Jiang, Changtao; Zhang, Zhipeng; Fu, Wei (Frontiers in Endocrinology, 2022)
Epidemiological studies have found an increased incidence of colorectal cancer (CRC) in people who undergo cholecystectomy compared to healthy individuals. The link between the gut microbiome and the occurrence and development of CRC is becoming clearer. However, due to the complexity of the microbial community, the mechanistic connections are less well understood. By summarizing the changes in the gut microbiome after cholecystectomy and the mechanisms of its potential influence on CRC, we aimed to unravel the interactions between the gut microbiota and its host and be better positioned to develop treatments for CRC after cholecystectomy.